Optimization of the Composition of Cocoa Pod and Coconut Shell Briquettes Based on SNI Quality Standards, Combustion Performance, and Technoeconomic Analysis - Munawar Yulianto; Bambang Sudarmanta (International Journal Labs, 2026)
This study aims to determine the optimal composition of cocoa pod–coconut shell briquettes based on quality parameters according to the Indonesian National Standard (SNI), combustion performance in a Natural Updraft Gasifier Stove–type biomass furnace, and technoeconomic aspects. The briquettes were produced in five compositional variations, namely KK100, KK75TK25, KK50TK50, KK25TK75, and TK100. The tests included moisture content, ash content, volatile matter, fixed carbon content, calorific value, energy density, ignition time, combustion rate, combustion duration, water boiling test, and energy cost analysis. The optimal composition was determined using the Multi-Criteria Scoring method, with weighting factors of 40% for SNI quality parameters, 40% for combustion performance, and 20% for technoeconomic aspects. The results showed that increasing the proportion of coconut shells reduced the moisture content from 14.67% to 4.53% and the ash content from 17.89% to 5.56%, while increasing the fixed carbon content from 45.05% to 71.14%. The highest calorific value was obtained for TK100 at 5,956 kcal/kg, while KK25TK75 produced a calorific value of 5,481 kcal/kg. In the combustion performance tests, TK100 exhibited the shortest ignition time (124 seconds), the longest combustion duration (191 minutes), and the shortest water boiling time (4 minutes). The technoeconomic analysis indicated that KK75TK25 had the lowest energy cost at 451.90 Rp/MJ and the highest energy-saving potential at 13.80%. The optimization results showed that TK100 achieved the highest overall score of 99.21. However, all briquette variations did not fully comply with SNI 01-6235-2000 because their volatile matter content exceeded the maximum allowable limit.